Pelatihan Pembuatan Soal bagi Guru Tingkat SMA (Jurnal KeDayMas: Kemitraan dan Pemberdayaan Masyarakat, 2022)
This program is designed to provide training to teachers in making questions at the high school (high school) level. This training is also a manifestation of efforts to improve and grow the ability to make the right and correct questions among teachers, especially all teachers in the Al-Asy'ari MA environment. This program begins with the material for forming the high school level question grid and forming the questions based on the high school level question grid. Furthermore, in the implementation of this program, all teachers look very enthusiastic in understanding the form of questions that are in accordance with the question grid. They discuss with other teachers when they have difficulty in preparing questions. Some of them also directly ask the abdimas team if they still didn't understand the material that had been delivered. The difficulty that is often faced by all teachers in this training is the selection of the types of questions that are in accordance with the abilities of students and the selection of the right language in arranging questions.